Genetic loss of the muscarinic M3 receptor markedly alters bile formation and cholestatic liver injury in mice. Issue 3 (26th August 2017) - Durchschein, Franziska; Krones, Elisabeth; Pollheimer, Marion J.; Zollner, Gernot; Wagner, Martin; Raufman, Jean‐Pierre; Fickert, Peter
Abstract : Aim: Hepatic innervation represents a potentially underestimated regulator of liver function and regeneration. The muscarinic 3 receptor (M3 ‐R) is the primary cholangiocyte receptor for the afferent parasympathetic innervation of bile ducts. We aimed to determine the specific role of the M3 ‐R in bile formation and models for cholestatic liver disease in mice. Methods: We compared bile flow and composition in M3 ‐R knock‐out mice (M3 ‐R −/− ) and wild type littermates (WT). Furthermore, we compared liver inury of M3 ‐R −/− and WT mice after 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine (DDC) feeding, a well‐characterized preclinical model of cholestatic liver disease. To analyze the possible role of the M3 ‐R as a therapeutic target, we treated 4‐week‐old Mdr2 −/− mice, a preclinical model for sclerosing cholangitis, with the M3 ‐R agonist bethanechol for 4 weeks. Results: M3 ‐R −/− mice showed significantly reduced bile flow compared to WT mice, most likely due to decreased biliary HCO3 − secretion. However, even aged M3 ‐R −/− mice did not spontaneously develop liver injury or cholestasis. Challenging M3 ‐R −/− and WT littermates with DDC feeding showed substantially aggravated liver injury in M3 ‐R −/− mice. After 4 weeks bethanechol treatment, Mdr2 −/− mice showed less liver injury compared to controls. Conclusion: Our experimental findings suggest that M3 ‐R‐signalling significantly influences bile formation. Loss of the M3 ‐R increases susceptibility to cholestatic injury in DDC‐fed mice. Since treatment of Mdr2 −/− mice with a M3 ‐R agonist decreases liver injury, M3‐R signaling may represent a therapeutic target in specific cholangiopathies.